Immersive worlds handbook - Lukas, Scott A (Abindgdon Taylor & Francis, 2013)
Scott Lukas is a key writer, speaker, and consultant on Themed Entertainment. He has written numerous books and articles on the subject of theme parks, shopping malls, themed spaces, video games and other contemporary consumer spaces. In the last five years, he has become a recognizable industry speaker and has provided keynote addresses and workshops in Germany, Orlando and California, including at the Themed Entertainment Association conference and Disney/ABC/Pixar events. He has been recognized with four teaching awards in his field.
Keywords: BUILDING TYPES (AR-BUIL)